Restricted access to innovative surgical technique related to a specific training, is it ethical? Example of the PIPAC procedure. A systematic review and an experts survey. (November 2020) - Martellotto, S.; Maillot, C.; Villeneuve, L.; Eveno, C.; Sgarbura, O.; Pocard, M.
Abstract: Objective: Using the example of Pressurized Intra Peritoneal Aerosol Chemotherapy (PIPAC), we analyse the development model of this procedure and provide an ethical analysis of the involvement of the industry in a new development. Summary background data: In the case of breakthrough innovation, medical training is essential for safe use of the new procedure. In some cases, pharmaceutical companies decide to organise this training. But when it becomes the only training opportunity to use the device, scientists and clinicians could be exposed to a conflict of interest? Methods: We performed a literature review of PIPAC publications using the STROBE criteria. Then, we conducted interviews with an expert panel to analyse the ethical impact of involvement of the industry in the development of the PIPAC procedure. Results: The number of publications has increased every year since the first publication in Germany, where the technology was developed in 2013. The scientific production was of good quality, with a mean STROBE score of 18.2 ± 2.4 out of 22 points. Ten of the 33 included studies declared a conflict of interest. From the interviews, the main axe concerning the implication of the industry was the training model. The company had decided that only trained and approval surgeon could perform the PIPAC procedure. All four interviewed practitioners agreed that it was initially a good way to implement the procedure safely, but later they felt uncomfortable about the control and validation by the industry. Conclusion: Based on the growing number of published papers from a growing number of international centres, the controlled training model is not limiting. However, the different levels of conflict of interest complicate transparency, and we postulated that this development model is limited to the beginning of the procedure diffusion. Clinicaltrial.gov registration: NCT04341337. Highlights: The surgical device used to perform PIPAC procedure is commercialized by a single manufacturer under a monopoly regimen. Formal training (economically supported by the manufacturer) is mandatory for surgeons who want to buy the device. This challenges our surgical practice from the ethical point of view. Based on the growing number of published papers from a growing number of international centres, the controlled training model is not limiting, and it is a successful model of development of this breakthrough innovation. But with the major involvement of the industry and the control of training, the different levels of conflict of interest complicate transparency.